FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PRODUKTVITAS PEKERJA SEKTOR PERTANIAN DAN INDUSTRI PENGOLAHAN - NFN Susilo (Jurnal Kependudukan Indonesia, 2011)
In the Province of East Java, the agricultural sector contributes the largest in employment, while its contribution to GDP is the lowest. On the other hand, the processing industry sector contributes the lowest in employment but its contribution to GDP is higher than the agricultural sector. Thereby it is important to study the productivity of both sectors. This study aims to examine the effect of sectoral attractiveness, individual characteristics and suitability ofjob options on the productivity of workers in the agricultural sector and manufacturing industry in East Java. Analysis of the data using a structural equation model (Structural Equation Modeling/SEM) and AMOS (Structural Analysis of Moment) application program. The study shows that the sectoral attractiveness and individual characteristics significantly influence the productivity of workers in both agriculture and manufacturing industry. But as an intermediate variable, the suitability ofjob options has no significant effect on workers' productivity. Thus, the effects of- sectoral attractiveness and individual characteristics on - workers productivity are direct.Keywords: the sectoral attractiveness, individual characteristics, suitability of job options, and labor productivity.